2021
DOI: 10.1097/wnr.0000000000001627
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Houttuynia cordata extract on propofol-induced injury of rat hippocampal neurons by regulating PI3K/Akt and Toll-like receptor 4/NF-κB signaling pathway

Abstract: Objective This study was to detect the protective effects of Houttuynia cordata extract on the damage induced by propofol in hippocampal neuron of rats. Methods Propofol-induced neuron injury model and H. cordata extract administration were conducted. Immunofluorescence and immunoblot were conducted for the effect of H. cordata extract on neuronal activity and inflammation were detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…It has been demonstrated that the ethanol extract of Houttuynia cordata Thunb can successfully reduce the oxidative damage to the liver and atherosclerosis brought on by a high-fat diet in rats [8]. Fang demonstrated that Houttuynia cordata Thunb extract could decrease the initiation of neuronal inflammation and apoptosis induced by propofol by enhancing neuronal activity [9]. Houttuynia cordata Thunb has shown good bacteriostatic activity against bacteria such as Staphylococcus aureus and Casecoccus [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the ethanol extract of Houttuynia cordata Thunb can successfully reduce the oxidative damage to the liver and atherosclerosis brought on by a high-fat diet in rats [8]. Fang demonstrated that Houttuynia cordata Thunb extract could decrease the initiation of neuronal inflammation and apoptosis induced by propofol by enhancing neuronal activity [9]. Houttuynia cordata Thunb has shown good bacteriostatic activity against bacteria such as Staphylococcus aureus and Casecoccus [10].…”
Section: Introductionmentioning
confidence: 99%